Game Edukasi Interaktif Sejarah Kerajaan Hindu-Buddha menggunakan Platform Scratch - Perkasa, Rizal Arindra Esa; Wantoro, Jan (Universitas Hamzanwadi, 2024)
The lack of effectiveness of traditional history learning methods at SMKN 1 Pedan. So, it is necessary to develop educational game learning media using the Scratch application, with the aim of fostering interest in learning and student involvement in learning the history of Hindu-Buddhist kingdoms. This research aims to produce and develop products in the form of learning media with a scratch platform for Hindu-Buddhist History subjects. This type of research is development by building or creating Scratch-based learning media. The method used in research to develop educational game media is Research and Development (R&D). The instruments used are media questionnaires, materials, observations, interviews and literature studies. The research model used is ADDIE with stages of analysis, design, development and implementation, and the data analysis technique used is descriptive statistics. Our findings show that the results of media testing are very feasible. Meanwhile, the response of users of this media in the category is very good. So, this game can be used by students to learn the History of Hindu-Buddhist Kingdoms in grade 10 SMKN 1 Pedan.